Virtue Ethics: The Misleading Category - Nussbaum, Martha (1999)
Virtue ethics is frequently considered to be a single category of ethical theory, and a rival to Kantianismand Utilitarianism. I argue that this approach is a mistake, because both Kantians and Utilitarians can, and do, have an interest in the virtues and the forrnation of character. But even if we focus on the group of ethical theorists who are most commonly called "virtue theorists" because they reject the guidance of both Kantianism and Utilitarianism, and derive inspiration from ancient Greek ethics, there is little unity to this group. Although there is a thin common ground that links all the group's members - a focus on the formation of character, on the nature of the passions, and on choice over the whole course of life - there are also crucial differences among them.